Impairment of lachrymal and salivary secretion and cellular immune responses to salivary antigens in rheumatoid arthritis. Issue 2 (April 1978) - Sullivan, S; Fernandes, L; McFarlane, I G; Wojcicka, B; Eddleston, A L; Doniach, D; Hamilton, E; Williams, R
Abstract : During a systematic investigation of 100 unselected outpatients with rheumatoid arthritis, 58 were found to have reduced lachrymal or salivary secretion. No correlation could be detected between the presence or absence of secretory abnormalities and the age or sex of the patient, the presence of nodules or salivary duct antibody, or the occurrence of vasculitis. However, there was a significant correlation between diminished salivary of lachrymal flow and the occurrence of cellular immune responses to a protein fraction of normal human saliva, sensitisation being found in 94% of those with impairment of salivary and lachrymal secretion as compared with 33% of those without.